2019
DOI: 10.1186/s12905-019-0728-z
|View full text |Cite
|
Sign up to set email alerts
|

Can mental health treatments help prevent or reduce intimate partner violence in low- and middle-income countries? A systematic review

Abstract: Background Epidemiological research suggests an interrelationship between mental health problems and the (re)occurrence of intimate partner violence (IPV). However, little is known about the impact of mental health treatments on IPV victimization or perpetration, especially in low- and middle-income countries (LMIC). Methods We conducted a systematic review to identify prospective, controlled studies of mental health treatments in LMIC. We defined ‘mental health treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 59 publications
(143 reference statements)
0
43
1
Order By: Relevance
“…For example, a trial currently underway in Congolese refugee camps in Tanzania seeks to evaluate an IPV intervention that integrates advocacy and structured psychosocial support; the authors argue that integrating this psychosocial support may render the preventive intervention more effective, vis-à-vis an intervention that focuses solely on advocacy [ 60 ]. Other recent literature has highlighted the limited evidence base around the effects of mental health interventions on the prevention and reduction of IPV [ 61 ], suggesting the potential importance of further exploring the role of targeted interventions addressing the nexus between IPV and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a trial currently underway in Congolese refugee camps in Tanzania seeks to evaluate an IPV intervention that integrates advocacy and structured psychosocial support; the authors argue that integrating this psychosocial support may render the preventive intervention more effective, vis-à-vis an intervention that focuses solely on advocacy [ 60 ]. Other recent literature has highlighted the limited evidence base around the effects of mental health interventions on the prevention and reduction of IPV [ 61 ], suggesting the potential importance of further exploring the role of targeted interventions addressing the nexus between IPV and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews have found that mental health treatments for common mental disorders and for alcohol misuse could effectively reduce IPV [ 75 , 76 ]. However, there is limited research on the impact of mental health treatment targeting depression on IPV perpetration instead of IPV victimization [ 75 ]. Further, there is limited evidence demonstrating the effectiveness of mental health interventions on IPV perpetration in low- and middle-income settings [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, men with HIV who are concurrently using alcohol and experiencing depressive symptoms may have fatigue or reduced energy, decreasing risk of alcohol-related IPV perpetration. Previous mental health interventions aiming to reduce IPV perpetration have either targeted participants who misuse alcohol or those who screen positive for depressive symptoms [ 75 ]. This study suggests that mental health interventions for men with HIV should target both groups—those who screen positive for hazardous drinking or depressive symptoms—to effectively reduce IPV perpetration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations